A holistic approach to promoting early child development: A cluster randomised trial of a group-based, multicomponent intervention in rural Bangladesh - Pitchik, Helen O; Tofail, Fahmida; Rahman, Mahbubur; Akter, Fahmida; Sultana, Jesmin; Shoab, Abul Kasham; Huda, Tarique Md. Nurul; Jahir, Tania; Amin, Md Ruhul; Hossain, Md Khobair; Das, Jyoti Bhushan; Chung, Esther O; et al. (BMJ Journals, 2022)
This article was published in the BMJ Global Health by BMJ Journals [© Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjgh-2020-004307 The Journal's website is at: https://gh.bmj.com/content/6/3/e004307